Prevalence of menopausal symptoms and its impact on Quality of life among menopausal women - D, Bhuvaneshwari.; Sarathi, Sathiyalatha (Journal of Neonatal Surgery, 2025)
Background: The life expectancy of midlife women has grown as a result of demographic and epidemiological shifts, which has led to an increase in the burden of morbidities associated with menopausal symptoms and has also had an impact on quality of life (QOL). Among rural midlife women in Gudur, India, aged 40 to 60 years, the purpose of this study is to investigate the prevalence of menopausal symptoms and its impact that these symptoms have on quality of life. The Components and Procedures: Using a random sample method, a community-based cross-sectional study was carried out on four hundred midlife women. For the purpose of determining the prevalence of menopausal symptoms and the quality of life, the menopause rating scale was utilised. Additionally, data were gathered for socio-demographic parameters, relevant menstrual history, and other variables. End Result: There was an 87.7% prevalence of menopausal symptoms, according to the findings. Anxiety was experienced by the majority of the people who participated in the research study (80%), followed by physical and mental tiredness (71.5%), sleep issues (61.2%), irritability (60.7%), joint and muscle discomfort (56%), and cardiac problems (54%). There were 36.7% of women who reported experiencing hot flushes, which is the most common symptom of menopause. Menopause occurred at a mean age of 47.53 years, with a standard variation of 4.5 years. Between the post-menopausal and peri-menopausal groups, a statistically significant difference was seen in the mean score of a few symptoms, including hot flushes, sweating (P < 0.003), and joint and muscle soreness (P < 0.014). Seventy-two percent of the people who participated in the research had a worse quality of life. The psychological symptoms were responsible for 70.8% of the lack of quality of life. The conclusion is that a comprehensive strategy, which includes modifications to lifestyle and behaviour, is essential in order to improve the quality of life (QOL) of these women and to reduce the menopausal symptoms they experience.